Participatory integrated assessment of scenarios for organic farming at different scales in Camargue, France. (March 2016) - Delmotte, Sylvestre; Barbier, Jean-Marc; Mouret, Jean-Claude; Le Page, Christophe; Wery, Jacques; Chauvelon, Phillipe; Sandoz, Alain; Lopez Ridaura, Santiago
Abstract: Alternative agricultural systems, such as organic farming (OF), are promising options to sustain both agriculture productivity and environmental health. However, the adoption of OF by farmers is occurring more slowly than is advocated. A key factor limiting farmers is an inability to predict socio-economic consequences of converting to OF. To overcome this, we developed a novel method of integrated assessment of agricultural systems (IAAS) and applied it to scenarios of development of OF in the Camargue region, South of France. In collaboration with the local stakeholders, we characterized the agricultural systems at different spatial scales and defined scenario related to the future of agriculture and to OF. We then used agent-based modeling with farmers and bio-economic modeling with local stakeholders for scenario assessment. We examined the effects on the development of OF systems of key factors such as the ongoing reform in the European Common Agricultural Policy and the effects of regulations for decreased use of pesticides. The policy reform implied trends towards a diversification of crops and greater possibility for conversion to OF. Development of OF at the regional level led to improved environmental performance, but caused a decrease in profitability of the rice supply chains. In light of the observed trade-off between rice production and OF development, objectives and options towards more sustainable agricultural systems were discussed with farmers and local stakeholders. Stakeholders' assessment of the framework provided insights on the positive and specific aspects of the IAAS methodology requiring improvement. The complementarities of agent-based and bio-economic modeling provide stakeholders with a better-informed assessment of diverse scenarios, for the development of more sustainable agricultural systems. Highlights: We target the participatory integrated assessment of agricultural systems. Scenarios related to organic farming were assessed with local stakeholders. We combined agent-based and bio-economic modeling to assess scenarios. The case study in Camargue reveals the complementarities between the models.